The Effect of Finger Grasp Relaxation on Reducing Pain Intensity in Patients - Sutiani, Asni Tri; Alamsyah , Mustopa Saepul; Mulyadi, Egi (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
This study aims to evaluate the effect of finger grasping relaxation technique on reducing pain intensity in postoperative patients in Arafat Room III RSI Assyifa Sukabumi City. Using a pre-experimental research design with a one-group pretest-posttest approach, this study involved 18 respondents selected through inclusion and exclusion criteria. Finger grasping relaxation technique, a simple non-pharmacological method, was performed to reduce pain by grasping fingers alternately for 3-5 minutes. The results of the analysis showed that the pain level of patients before the intervention was dominated by the moderate pain category (72.2%), while after the intervention the majority of patients experienced mild pain (66.7%). Statistically, there was a significant decrease in patients' pain levels, with a p value <0.05 based on the paired sample t-test. The mean pain level before the intervention was 4.16, decreasing to 3.00 after the intervention, showing a mean difference of 1.16. This study supports the effectiveness of the finger grasp relaxation technique as a supportive therapy to reduce postoperative pain. This technique stimulates the release of endorphins that inhibit pain signals, promote relaxation, and reduce physical and emotional stress. These results are consistent with previous studies showing significant benefits of this technique in reducing pain intensity. In conclusion, finger grasp relaxation is an effective, safe, and easy-to-implement method as a non-pharmacological therapy to help with postoperative pain management, and can be used as an alternative or companion to pharmacological therapy. This study makes a significant contribution to nursing practice, particularly in pain management.